Declining heart health in Pakistan! A hidden or less studied monster? - Abbasi, Faizan; Abbasi, Qurat-ul-Ain; Zain Ul Abideen, (Journal of the Pakistan Medical Association, 2026)
Dear Editor Heart failure (HF) is a life-threatening condition carrying high morbidity and mortality, affecting more than 64 million people worldwide [1]. It also affects patients' quality of life, is a financial burden, prevents them from carrying out normal daily activities, working, and playing sports, and sometimes causes long hospital stays. Although aging affects heart health, a more alarming situation is when this devastating disease starts affecting the youth and middle-aged population. A recent study based on the analysis by the British Heart Foundation shows heart health in the UK is declining in worrying trends, with alarming numbers, which are an 18% increase in cardiovascular deaths in working-age adults (2019–2023). 21% increase in HF diagnoses (2020–2024), and a12% rise in diabetes diagnoses (2020–2024), which is a major risk factor for cardiovascular diseases (CVDs). There has been 83% rise in heart hospital treatment waiting lists in England (2020–2025) [2]. Data from other studies suggest that mortality in the younger population (20-44 years) is higher stating the statistics of 3.9% at 30 days, 12.4% at one year, and 27.7% at five years [3]. Potential causes of these are sedentary lifestyle, environmental factors, impact of Covid-19, which causes disrupted routine healthcare checkups and delayed diagnosis —lengtheningwaiting lists in the NHS for heart-related treatments, socioeconomics issues, unhealthy food and substance abuse and genetic predisposition [1] [4]. In Pakistan, most of the studies focus on CADs, but limited data is available on HF in the younger population, and that limited data suggests that the prevalence of heart failure in the younger population is also on the rise in their as their 30s and 40s is also rising, driven by the early onset of CVDs. The risk factors for HF are also the same as CADs, including smoking, diabetes mellitus, and sedentary lifestyle, along with substance misuse. Large-scale, focused studies on heart failure in the young are needed in Pakistan. Enhanced cardiac screening and early detection of cardiovascular risk factor, more investment in healthcare structure to manage CVD, public health awareness campaigns promoting healthy lifestyle should run to combat this imminent threat [5]. As results from UK studies demonstrate the scale of the problem, similar proactive measures in Pakistan would enable timely intervention to reduce heart-related morbidity and mortality.